ECONOMIC EFFECTS IN THE PRODUCTION OF LEADING FRUIT VARIETIES - Vukoje, Vеljko; Milić, Dušan (Economics of Agriculture, 2009)
The comparative analysis of paramount parameters of success clearly indicates that pear production is the most cost-effective followed by apple and plum production. Within pear production, the highest production value (818250 RSD per hectare) has been established, alongside the highest gross margin (607721 RSD per hectare) and the highest profit (557194 RSD per hectare). Pear production is estimated to have the highest production efficiency (3,13) and the highest profit rate (68,1%). The results of the sensitivity analysis indicate that the analysed productions comprise significant capacity in obtaining positive financial results due to their resilience to the decrease in yield and/or market price of products (from 49% in plum production to 75% in pear production).